Imaging collagen packing dynamics during mineralization of engineered bone tissue. (1st September 2015) - Campi, G.; Fratini, M.; Bukreeva, I.; Ciasca, G.; Burghammer, M.; Brun, F.; Tromba, G.; Mastrogiacomo, M.; Cedola, A.
Graphical abstract: Abstract: The structure and organization of the Type I collagen microfibrils during mineral nanoparticle formation appear as the key factor for a deeper understanding of the biomineralization mechanism and for governing the bone tissue physical properties. In this work we investigated the dynamics of collagen packing during ex-vivo mineralization of ceramic porous hydroxyapatite implant scaffolds using synchrotron high resolution X-ray phase contrast micro-tomography (XPCμT) and synchrotron scanning micro X-ray diffraction (SμXRD). While XPCμT provides the direct 3D image of the collagen fibers network organization with micrometer spatial resolution, SμXRD allows to probe the structural statistical fluctuations of the collagen fibrils at nanoscale. In particular we imaged the lateral spacing and orientation of collagen fibrils during the anisotropic growth of mineral nanocrystals. Beyond throwing light on the bone regeneration multiscale process, this approach can provide important information in the characterization of tissue in health, aging and degeneration conditions. Statement of Significance: BONE grafts are the most common transplants after the blood transfusions. This makes the bone-tissue regeneration research of pressing scientific and social impact. Bone is a complex hierarchical structure, where the interplay of organic and inorganic mineral phases at different length scale (from micron to atomic scale) affect its functionality and health. Thus, the understanding of bone tissue regeneration requires to image its spatial-temporal evolution (i) with high spatial resolution and (ii) at different length scale. We exploited high spatial resolution X-ray Phase Contrast micro Tomography and Scanning micro X-ray Diffraction in order to get new insight on the engineered tissue formation mechanisms. This approach could open novel routes for the early detection of different degenerative conditions of tissue.